IFFCO TOKIO in the service of rural India - Suri, H O (Indian Farming, 2017)
The IFFCO Tokio has undertaken many activites in various villages and tribal areas Integrated Rural Development Project. It has embarked upon very meaningful CSR activites for the the general well being of poor segment of population across the states of Rajasthan and Odisha.